Electronically Delivered Support to Promote Intervention Implementation Fidelity: A Research Synthesis. Issue 2 (17th March 2022) - Fallon, Lindsay M.; Collier-Meek, Melissa A.; Famolare, Gianna M.; DeFouw, Emily R.; Gould, Kaitlin M.
Abstract: The coronavirus (COVID-19) pandemic has led to many students receiving remote instruction. As educators support students' learning and behavior from a distance, school psychologists can utilize their consultation skills to offer educators implementation support to ensure interventions implemented are maximally successful. Although the effectiveness of intervention implementation supports (such as direct training and performance feedback) has been well documented, most existing studies involved providing implementation support in person. The purpose of this study was to synthesize single-case research design studies that examined electronically delivered implementation supports (EDIS) to school personnel (e.g., teachers, paraeducators) to promote implementation fidelity. One hundred and seventy-four articles were screened and 12 studies were coded for characteristics of EDIS upon being determined to meet research design quality standards outlined by the What Works Clearinghouse. Results of the review indicated that, overall, studies identified were conducted with sufficient methodological rigor and effect sizes estimates indicated EDIS promoted high levels of intervention implementation. We translate these research findings to guide practitioners' actions. Implications include EDIS being considered for interventions provided to students involved in distance learning, including those engaged in schooling at home due to COVID-19. Impact Statement This systematic review examined the effect of electronically delivered implementation support (EDIS) on educators' implementation fidelity. Following rigorous screening and coding procedures, 12 studies containing 46 individual cases met research design standards outlined by the What Works Clearinghouse and were included in the synthesis. As a result of this review, the authors concluded that EDIS may be useful to school psychologists supporting educators from a distance to implement interventions with youth who may be engaged in schooling remotely.